COVID-19 Epidemiology in our Country and the World - Buran, Duran; Uğraş Dikmen, Asiye (Turkey Health Literacy Journal, 2021)
COVID 19 was seen for the first time in Wuhan, China on 31 December 2019. The epidemic spread to other countries in the Far East in a short time. The virus has started to appear in the Americas, Europe and Africa in a short period of time. The virus was then seen for the first time in Turkey on March 11. The virus has spread throughout World countries so rapidly that, the World Health Organization (WHO) announced a pandemic in March 2020. Transmission mainly occurs via close contact through respiratory droplets. Another way of transmission is indirect (secondary) form; which occurs by touching a contaminated surface and then touching person’s eyes, nose, or mouth. In this process, some groups such as elderly people, healthcare workers and people with comorbidities are more risky in terms of outbreak. In the world and our country where the number of infected people and deaths are increasing every minute, control of the virus has not been fully achieved. As of the end of December 2020, there were over 80 million cases and nearly 2 million deaths in the world due to the epidemic. COVID-19 is a serious global public health problem. Therefore, it is important to adhere to individual and social measures. In this article, the source, transmission pathways, clinical characteristics, risk groups and epidemiology of COVID-19 are examined.
Keywords: COVID-19; Pandemic; Epidemiology